The global incidence of bullous pemphigoid: a systematic review and meta‐analysis. (1st March 2022) - Persson, M.S.M.; Begum, N.; Grainge, M.J.; Harman, K.E.; Grindlay, D.; Gran, S.
Summary: Background: Bullous pemphigoid (BP) is an autoimmune blistering disorder that mainly affects older people. Although the disease is associated with considerable morbidity and mortality, the burden of disease worldwide is unclear. Objectives: The study aim is to pool the global incidence of BP and determine whether this varies according to geographic area, age group, setting and study quality. Methods: Ovid MEDLINE, Ovid Embase and grey literature were systematically searched on 7 April 2020. Two reviewers independently screened, extracted data and appraised each study's quality using the Joanna Briggs Institute critical appraisal tool. Two domains, indicative of selection and survey bias, were used to identify high‐quality studies. The cumulative incidence was standardized to 1 year and pooled in a random‐effects meta‐analysis. Subgroup and sensitivity analyses were conducted. Results: Twenty‐seven studies were identified, of which 23 provided cumulative incidence and four provided incidence rates. The cumulative incidence of BP was 8·2 [95% confidence interval (CI) 4·8–13.7] per million people whereas the incidence rate was 34·2 (95% CI 19·2–60·7) per million person‐years. Of the continents that contributed more than one study, the cumulative incidence was 10·3 (95% CI 5·8–18·2) and 5·6 (95% CI 3·5–9·0) per million people in Europe and Asia, respectively. The incidence was highest in studies including adults only ( n = 2), in population‐based studies ( n = 9) and in more recent years. The cumulative incidence was higher (13·3 per million people, 95% CI 6·0–29·5) when restricting the analysis to higher‐quality studies ( n = 11). High heterogeneity ( I 2 > 82%) was observed across all pooled estimates. Conclusions: The incidence of BP varies globally, is generally low but appears to be increasing over time. The burden of disease is likely to be underestimated.